Factors associated with drug-related harms related to policing in Tijuana, Mexico - Patterson Thomas L; Anderson Christy M; Lozada Remedios; Volkmann Tyson; Vera Alicia; Strathdee Steffanie A (BMC, 2011)
Abstract Objective To assess factors associated with drug-related harms related to policing among injection drug users (IDUs) in Tijuana, Mexico. Methods IDUs who were over 18 years old and had injected drugs within the last six months were recruited via respondent-driven sampling and underwent questionnaires and testing for HIV (human immunodeficiency virus), syphilis and TB (tuberculosis). Random effects logistic regression was used to simultaneously model factors associated with five drug-related harms related to policing practices in the prior six months (i.e., police led them to rush injections; affected where they bought drugs; affected locations where they used drugs; feared that police will interfere with their drug use; receptive syringe sharing). Results Of 727 IDUs, 85% were male; median age was 38 years. Within the last 6 months, 231 (32%) of IDUs reported that police had led them to rush injections, affected where they bought or used drugs or were very afraid police would interfere with their drug use, or shared syringes. Factors independently associated with drug-related harms related to policing within the last six months included: recent arrest, homelessness, higher frequencies of drug injection, use of methamphetamine, using the local needle exchange program and perceiving a decrease in the purity of at least one drug. Conclusions IDUs who experienced drug-related harms related to policing were those who were most affected by other micro and macro influences in the physical risk environment. Police education programs are needed to ensure that policing practices do not exacerbate risky behaviors or discourage protective behaviors such as needle exchange program use, which undermines the right to health for people who inject drugs.